Palmeiras’ Ecosystem: The Key-Attributes Which Interfere in the Fans’ Judgments - Coutinho da Silva, Edson; Luzzi Las Casas, Alexandre (British Journal of Marketing Studies, 2019)
Objective: This article aims to understand and analyse which fans’ attributes most interferes with their view concerning the sports ecosystem of the Palmeiras Sports Society for sporting events. Methodology: an exploratory research was carried out comprising 84 topics using the Likert scale to be administered to 309 sports fans in 3 matches between February and March 2017. The analysis procedure followed three steps: (i) calculating the chi-square testes cross tables; (ii) selecting the topics which achieved less than 5% significance; (iii) and identifying that group of fans’ attributes that are most similar and most divergent. Findings: monthly salary is the most critical fan attribute. Palmeiras’ fans believe that leagues are the critical dimension; club management is the second dimension most divergent. Conclusion: Therefore, all of the 3 hypotheses were confirmed. Palmeiras’ managers have invested money and energy to implement the business and marketing principles.